Modern approaches to surgical treatment of individual uterine fibroids in pregnant women: ethics and pathology (literature review) - A. A. Azizova; K. Ya. Kashnikova; A. A. Andrushchenko; Kh. A. Nadzhafov; E. I. Pogiba; M. A. Sergievskiy (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Uterine fibromyoma is a common benign formation that can complicate the course of pregnancy. Modern approaches to the surgical treatment of this pathology in pregnant women require special attention from the point of view of ethics and safety for both mother and fetus. The relevance of this topic is due to the growing number of pregnant women with fibromyomas, which requires the development of optimal treatment strategies. The aim of the study is to analyze modern methods of surgical intervention for uterine fibromyoma in pregnant women, as well as to assess the ethical aspects and possible risks associated with such interventions. Materials and methods. The authors analyzed the domestic and foreign literature on the surgical treatment of uterine fibromyoma in pregnant women, applied a sociological method and content analysis. The analysis was carried out using data obtained from various sources: medical recommendations, follow-up results and clinical recommendations. Results. It turned out that modern surgical methods, such as laparoscopic myomectomy, are the most effective for the treatment of uterine fibromyoma in pregnant women. They have a minimal number of complications and have a positive effect on the course of pregnancy. Conclusions. Timely diagnosis, an integrated approach to patient management and the use of modern treatment methods, including laparoscopic myomectomy, can minimize risks, improve pregnancy and childbirth outcomes, and improve women's quality of life.